The performance of GeneXpert® PCR assay in detecting group B streptococcus colonization at labor - Mohammed Rohi Khalil; Jens Kjølseth Møller; Stine Yde Nielsen (IMR Press, 2021)
Background: The aim of this study was to assess the performance of GeneXpert® group B streptococcus (GBS) PCR assays in a Danish setting, using rectovaginal GBS culture at labor as the gold standard. Methods: Three hundred and sixty-six (366) women with one or more of the following risk factors for GBS carriage-GBS during current pregnancy, prior infant with EOGBS, temperature >38.0 ∘C during labor, preterm labor <37 weeks of gestation, rupture of membranes ≥18 hours-were included in the study. Intrapartum rectovaginal swab samples were tested at the bedside by GeneXpert® GBS PCR assay, and cultured on agar plates (Granada) with and without prior use of growth-selective enrichment broth. Results: The GeneXpert® GBS PCR assay showed a sensitivity of 91.7%, a specificity of 97.2%, a PPV of 92.6 %, and a NPV of 96.8%. The turnaround time of the assay was 50 minutes. Conclusions: The GeneXpert® has a high performance, indicating that the assay can be used in a clinical setting.